2004
DOI: 10.1161/01.hyp.0000133692.47754.e5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fetal-Type Smooth Muscle Cells in the Media of Microvessels From Hypertensive Patients

Abstract: Abstract-Significant structural and functional changes in smooth muscle cells (SMCs) of microvessels (diameter 30 to 300 m) occur in hypertension. However, in microvessels of hypertensive patients, the differentiation pattern of SMCs underlying such changes remains undefined. To analyze the differentiation pattern of SMCs (adult, postnatal, or fetal), 49 muscle biopsies (rectus abdominis) were analyzed: 16 from children (aged 11 months to 11 years), 15 from normotensive adults (aged 55 to 74 years), 18 from hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Reactivation of antenatal gene expression profiles and cellular phenotypes has been shown in several adult organs and tissues subjected to injury, including the myocardium and blood vessels. 64, 65 Therefore, the discovery of the embryonic endothelial-to-hematopoietic transition (EHT) has important implications for interpretation of the EPC phenotype and vascular biology in general. 66 Genetic and epigenetic studies of the hemato-endothelial origin and fate of putative EPC phenotypes, as well as of the EHT in vitro are important future challenges in this research area (Table 1).…”
Section: Characterisation Of Epcsmentioning
confidence: 99%
“…Reactivation of antenatal gene expression profiles and cellular phenotypes has been shown in several adult organs and tissues subjected to injury, including the myocardium and blood vessels. 64, 65 Therefore, the discovery of the embryonic endothelial-to-hematopoietic transition (EHT) has important implications for interpretation of the EPC phenotype and vascular biology in general. 66 Genetic and epigenetic studies of the hemato-endothelial origin and fate of putative EPC phenotypes, as well as of the EHT in vitro are important future challenges in this research area (Table 1).…”
Section: Characterisation Of Epcsmentioning
confidence: 99%
“…The structure of small arteries in humans is studied by biopsies taken from subcutaneous fat. 33,34 Capillary rarefaction in humans is studied by capillaroscopy of the nail fold microvasculature in vivo. 7,10,15 Microvascular rarefaction and disadvantageous branching geometry, 35,36 and a narrower arteriolar caliber [37][38][39] are also found in the retinal microcirculation of hypertensive patients.…”
Section: The Microvasculature Is Rarefied In Hypertensionmentioning
confidence: 99%
“…In the last three decades, several researches demonstrated that hypertension is associated with remodeling of the arterial wall, a process mainly characterized by changes in quantitative/qualitative composition of the ECM as well as synthetic/proliferative VSMC differentiation [22][23][24]. Elastic fibers, a major constituent of large arterial conduits, are composed of an elastin core surrounded by fibrillin-rich microfibrils [25].…”
Section: Hypertensive Remodeling Of Large Arterial Conduits: Is It Famentioning
confidence: 99%